Analisis Kepatuhan Syariah pada Wisata Halal Lafa Park Adventure - M. Padly; MH Ainulyaqin; Kisanda Midisen; Sukron Mamun; Sakum (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to analyze sharia compliance in halal tourism Lafa Park Adventure if it adheres to the principles of sharia. Lafa Park Adventure halal travel is a type of travel. with a sharia design founded by Mr. H. Irfan Amirudin aims to spread Islam by promoting sharia principles and educating sunnah activities recommended by the Prophet Muhammad SAW such as swimming, horse riding and archery. To determine whether the rides and facilities are in accordance with sharia, academics will conduct a study, researchers will then elucidate the halal tourist indicators. The research employed a qualitative methodology along with the method of field study. In theory, researchers will map informants that include of tourist attraction managers and tourists. Basically, the results show that Lafa Park Adventure halal tourism has implemented sharia compliance with the benchmarks of the MUI DSN Fatwa NO: 1 08/DSN-MUI/X/2016. In addition, Lafa Park Adventure Tourism is suggested to be a pilot for the local government as halal tourism because many integrated Islamic schools need tourist facilities like this that prioritize sharia principles and the sunnah of the prophet Muhammad SAW as a good education for children.